Public Speaking sebagai Strategi untuk Meningkatkan Keterampilan Bernalar Kritis Siswa Sekolah Dasar - Alviansyah, Muhammad Daffa Rizky; Abduh, Muhammad (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study investigates the impact of participation in public speaking extracurricular activities on the critical thinking skills of elementary school students. Utilizing a quantitative ex-post facto design, the research involved a saturated sample of 10 students enrolled in the public speaking program at SD Muhammadiyah PK Baturan. A written test instrument, developed based on critical thinking indicators and contextual student experiences, was used for data collection. Data were analyzed through simple linear regression. Validity and reliability tests confirmed that the instrument met appropriate measurement standards. The hypothesis testing revealed a significant effect of public speaking participation on students’ critical thinking skills (p < 0.001), with an R² value of 0.843, indicating that 84.3% of the variance in critical thinking skills is explained by students’ involvement in the activity. The findings suggest that public speaking extracurriculars play a substantial role in enhancing students' critical reasoning and present a promising avenue for supporting 21st-century learning competencies.